2003
DOI: 10.1159/000068473
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of Outer Stratum corneum in Hereditary Palmoplantar Keratodermas

Abstract: Background: The analysis of lipid composition of the outer stratum corneum is a promising approach to study the pathophysiology of inherited disorders of keratinization. Objective: The purpose of the study was the search for biochemical alterations of stratum corneum lipids in hereditary palmoplantar keratoderma (PPK). Methods: Using high-performance thin-layer chromatography, we performed an analysis of all major stratum corneum lipid classes in scales of 29 patients with 8 different types of hereditary PPK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We found an accumulation of neutral lipid droplets in the stratum corneum of paw skin of Slurp1 −/− mice. In earlier studies, lipid droplets were observed in the fingernails of mal de Meleda patients ( Salamon, 1986 ; Salamon et al , 1984 ), and higher triglyceride levels were also found in the epidermis of several mal de Meleda patients ( Kuster et al , 2003 ). The increased numbers of lipid droplets in the stratum corneum are likely due to impaired hydrolysis of triglycerides, a process that is essential for the formation of acylceramides and the epidermal water barrier ( Elias et al , 2008 ).…”
Section: Discussionmentioning
confidence: 86%
“…We found an accumulation of neutral lipid droplets in the stratum corneum of paw skin of Slurp1 −/− mice. In earlier studies, lipid droplets were observed in the fingernails of mal de Meleda patients ( Salamon, 1986 ; Salamon et al , 1984 ), and higher triglyceride levels were also found in the epidermis of several mal de Meleda patients ( Kuster et al , 2003 ). The increased numbers of lipid droplets in the stratum corneum are likely due to impaired hydrolysis of triglycerides, a process that is essential for the formation of acylceramides and the epidermal water barrier ( Elias et al , 2008 ).…”
Section: Discussionmentioning
confidence: 86%
“…In tissues that experience constant mechanical trauma, such as palmoplantar epidermis, the presence of only one functional DSG1 allele is apparently not sufficient to ensure tissue integrity and proper regulation of epidermal proliferation and differentiation. The resulting disturbances of the process of cornification and desquamation are usually also associated with defects in epidermal lipid metabolism or lipid organization as epiphenomenon as noted in various forms of hereditary KPP [26]. Recently, it has been shown that desmosome structure and the relative expression of desmosomal components are different in the palm, a trauma and weight-bearing region, when compared with breast skin [27].…”
Section: Discussionmentioning
confidence: 99%